DETECTING PARENTAL DECEPTION USING A BEHAVIOR RATING SCALE DURING ASSESSMENT OF ATTENTION‐DEFICIT/HYPERACTIVITY DISORDER: AN EXPERIMENTAL STUDY. Issue 2 (28th December 2015) - Norfolk, Philip A.; Floyd, Randy G.
Abstract : It is often assumed that parents completing behavior rating scales during the assessment of attention‐deficit/hyperactivity disorder (ADHD) can deliberately manipulate the outcomes of the assessment. To detect these actions, items designed to detect over‐reporting or under‐reporting of results are sometimes embedded in such rating scales. This study presents the results of an experimental study in which parents (a) read a scenario telling them that their hypothetical son's teacher has suggested their son may have ADHD and (b) considered assigned goals for the assessment. Parents then completed the accompanying Conners 3Parent Short form (Conners 3‐P[S]) in a manner that they believed would achieve their assigned goals. Findings showed that parents are able to engage in deception when completing behavior rating scales. The validity scales embedded in the Conners 3‐P(S), however, demonstrated mixed results for detecting parental deception with the Negative Impression validity scale, accurately detecting attempts to malinger in the majority of cases, whereas the Positive Impression validity scale appears to have little to no diagnostic utility for the detection of defensive responding. Clinicians utilizing behavior rating scales should carefully consider results, and nonresults, obtained from embedded validity scales when interpreting parent responses to behavior rating scales as part of an ADHD assessment.